Ernesto Kiza, Tödliche Grenzen – Die fatalen Auswirkungen europäischer Zuwanderungspolitik (Münster: Lit Verlag, 2008) - Markus Meckl (Nordicum-Mediterraneum, 2010)
A review of Ernesto Kiza's Tödliche Grenzen, concerning migration and European policies on migrants